Understanding The Impact of Service Recovery Strategies Towards Service Recovery Satisfaction and Customer Loyalty: A Case of IndiHome Internet Service Provider (Journal of Business and Management, 2021)
IndiHome is one of internet service providers in Indonesia. Despite the increasing number ofusers, IndiHome experience service failure in serving their customers. To understand the impact of service recovery strategies towards service recovery satisfaction and customer loyalty, IndiHome have to performed service recovery. Quantitative method is used to gain the information in order to identify the relationship between service recovery strategies towards service recovery satisfaction and customer loyalty. The primary data is gathered from 230 respondents with several criteria. The results shows that compensation is the only strategies that affects both service recovery satisfaction and customer loyalty, and the other just affect service recovery satisfaction. Also, IndiHome have to implement some strategies of service recovery to particular type of respondents based on what type of service recovery strategies that the customers tend to be more focused or concerned in order to gain back their satisfaction and maintain their loyalty. Therefore, the objective of this research is completed. Keywords: Problem Solving, Explanation, Compensation, Follow Up, Service Recovery Strategies, Service Recovery Satisfaction, Customer Loyalty.